A facile strategy to fabricate phosphorus-free and halogen-free flame retardant polyacrylonitrile fiber based on amidoximation and Fe (III) ion chelation. (September 2022) - Liu, Yansong; Zhao, Wenjing; Yu, Xi; Zhang, Jiayue; Ren, Yuanlin; Liu, Xiaohui; Qu, Hongqiang
Highlight: A novel and facile strategy was developed to fabricate flame retardant polyacrylonitrile fibers. Amidoximation and Fe (III) ion chelation endows polyacrylonitrile fibers excellent flame retardancy. The preparation process was environmental-friendly and sustainable. Abstract: In this work, we proposed a novel phosphorus-free and halogen-free strategy to prepare flame retardant polyacrylonitrile fibers (FR-PAN). First, PAN fibers were modified with hydroxylamine hydrochloride (HA) to introduce amidoxime groups in PAN fibers (A-PAN), then the A-PAN samples were immersed in ferric chloride solution to chelate Fe 3+ to obtain FR-PAN. The micro calorimeter (MCC) test showed that the peak heat release rate (PHRR) and total heat release (THR) of FR-PAN were reduced by 72.9%, and 86.9% respectively. Meanwhile, the limiting oxygen index (LOI) value of FR-PAN increased from 17.0% to 36.7%. TG results demonstrated that amidoxime groups promoted the cyclization and dehydrogenation of PAN in advance. Meanwhile, the released nonflammable NH3 effectively diluted the emission of combustible gases, which acted as a flame retardant role in gas-phase. Fe 3+ had synergistic catalytic char formation effect, resulting in a highly dense char layer containing Fe2 O3, which isolated oxygen, significantly reduced the emission of toxic gases. This work endowed PAN fibers with good flame retardancy and great potential application in the field of functional fibers. Graphical abstract: Image, graphical abstract